The Impact of CSR Environmental Disclosure and Institutional Ownership on Company Value - Shifa, Dzauqy; Harto, Puji (LifeSciFi, 2024)
The implementation of CSR environmental disclosure and the degree of institutional ownership by companies influences the reduction of information asymmetry and increase firm value. The implementation of good CSR environmental disclosure by following regulations and with supervision carried out by existing institutional ownership can increase information transparency which can reduce information asymmetry which ultimately increases investor confidence in a company to increase firm value. This study investigates the relationships among CSR environmental disclosure, institutional ownership levels, firm value, and information asymmetry as a mediating factor. The research utilizes a dataset of 270 observations from companies listed in the LQ45 Index spanning from 2013 to 2022. According to the findings of the PLS analysis, CSR environmental disclosure exerts a direct negative impact on firm value and indirectly affects it through information asymmetry as a mediator. Similarly, institutional ownership does not have a direct negative impact on firm value, but it significantly diminishes firm value through its influence on information asymmetry as a mediating variable.